Nitric oxide-mediated immunosuppression following murine Echinococcus multilocularis infection - DAI, W J (Blackwell Science Inc, 1999)
In some parasitic infections immunosuppression is a prominent characteristic of the host–parasite interplay. We have used a murine alveolar echinococcosis (AE) model in susceptible C57BL/6 mice to document a suppressed splenocyte proliferative response to concanavalin A (Con A) at the early (1-month) stage and to Echinococcus multilocularis-crude antigen (Emc-antigen) at the late (4–6-month) stage of chronic infection. Despite proliferative suppression, splenic cytokine production [interleukin-2 (IL-2), IL-4 and interferon-γ (IFN-γ)] in response to Con A or Emc-antigen stimulation was not suppressed at 1 month postinfection (p.i.). Infection resulted in a strong Mac-1(+) cell infiltration of the peritoneal cavity and spleen. Peritoneal cells (PEC) from mice infected at the 1-month stage were rich in macrophages and expressed significantly higher levels of transcripts for the inflammatory cytokine IL-1β and for tumour necrosis factor-α and inducible nitric oxide synthase (iNOS), when compared with PEC from non-infected control mice. Conversely, the IL-10 transcript level remained low and did not change during infection. Spleen cells supplemented with PEC from infected mice induced a marked increase in the levels of nitrite in response to Con A and Emc-antigen stimulation, and also a complete suppression of splenic proliferation. The spleen cells from late-stage infected mice expressed only background levels of IL-10 but greatly increased levels of iNOS, when compared with normal spleen cells. This observation correlated with the immunosuppression demonstrated at the late stage of murine AE. Furthermore, the suppressed splenic proliferative responses observed at the early and late stage were reversed to a large extent by the addition of N(G)-monomethyl-l-arginine and partially by anti-IFN-γ. Thus, our results demonstrated that the immunosuppression observed in chronic AE was not primarily dependent on IL-10 but rather on nitric oxide production by macrophages from infected animals.